Determinants of Banks‘ Profitability: An Applied Study on Jordanian Banks Listed on the Amman Stock Exchange - Twairesh, Abdulla Ewayed (The Arab Journal of Administration, 2024)
This study aimed to examine the internal determinants of bank profitability of Jordanian banks. Because of specific study objectives, this study excludes the external factors of profitability to find the role of bank internal determinants in achieving high performance using panel data regression. Fixed effect panel regression analysis built on balanced panel data using 12 commercial banks over the sample period of (2005-2021). The study used two variables to measure the banks’ profitability; return on assets (ROA) and return on equity (ROE), while the independent variables included loans to deposit ratio. Liquidity ratio. Credit risk, expense control, and equity to total assets. The results obtained from the profitability model indicated that there is an inverse effect of the ratio of loans to deposits, Liquidity ratio, credit risks, and expense control on the profitability of Jordanian banks listed on the Amman Stock Exchange measured by return on assets and return on equity. While equity to total assets had a positive impact on the profitability of Jordanian bank. The study recommended that banks ‘ management pay attention to the ratio of loans to deposits and liquidity ratio and efficiently manage operational expenses, because of their impact on the profitability of banks.